2020
DOI: 10.1134/s1070428020080023
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of 1,3-Disubstituted Ureas and Their Isosteric Analogs Containing Polycyclic Fragments: IV.1 1-(Bicyclo[2.2.1]hept-5-en-2-yl)-3-(fluoro, chlorophenyl)ureas

Abstract: The reaction of bicyclo[2.2.1]hept-5-en-2-yl isocyanate with fl uoro-and chloro-substituted anilines was used to synthesize in a yield of 25-68% a series of 1,3-disubstituted ureas containing a lipophilic group in their structure. The synthesized ureas are promising as inhibitors of RNA virus replication and human soluble epoxide hydrolase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Wang et al [14] reported the synthesis of unsymmetrical ureas with a 3-fold excess of CDI. For example, 1-(6-bromo [1,2,4]triazole[1,5-a]pyridin-2-yl)-3-methylurea was synthesized in a yield of 79.6% by heating a mixture of 6-bromo [1,2,4]triazole[1,5-a]pyridin-2-amine NaH and a 3-fold excess of CDI in DMF at 60°C followed by adding a 3,5-fold excess of methylamine and heating at 60°C for 6 h. The authors of the cited work did not mention whether they removed excess CDI before adding the second amine.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al [14] reported the synthesis of unsymmetrical ureas with a 3-fold excess of CDI. For example, 1-(6-bromo [1,2,4]triazole[1,5-a]pyridin-2-yl)-3-methylurea was synthesized in a yield of 79.6% by heating a mixture of 6-bromo [1,2,4]triazole[1,5-a]pyridin-2-amine NaH and a 3-fold excess of CDI in DMF at 60°C followed by adding a 3,5-fold excess of methylamine and heating at 60°C for 6 h. The authors of the cited work did not mention whether they removed excess CDI before adding the second amine.…”
mentioning
confidence: 99%
“…we studied the reaction of amine 2 with CDI in the absence of another amine. According to the GCMS data, mixing amine 2 with CDI at 25°C results in a fairly rapid (20 min) formation of intermediate carboxamide 6 [Scheme 3, reaction(1)]. However, this reaction, too, gave symmetrical urea 5f (yield 8%), which can…”
mentioning
confidence: 99%
See 1 more Smart Citation